NOTCH4 signaling controls EFNB2-induced endothelial progenitor cell dysfunction in preeclampsia. Issue 1 (July 2016) - Liu, Xiaoxia; Luo, Qingqing; Zheng, Yanfang; Liu, Xiaoping; Hu, Ying; Liu, Weifang; Luo, Minglian; Zhao, Yin; Zou, Li
Abstract : Preeclampsia is a serious complication of pregnancy and is closely related to endothelial dysfunction, which can be repaired by endothelial progenitor cells (EPCs). The DLL4/NOTCH–EFNB2 (ephrinB2) cascade may be involved in the pathogenesis of preeclampsia by inhibiting the biological activity of EPCs. In addition, both NOTCH1 and NOTCH4, which are specific receptors for DLL4/NOTCH, play critical roles in the various steps of angiogenesis. However, it has not been determined which receptor (NOTCH1, NOTCH4, or both) is specific for the DLL4/NOTCH–EFNB2 cascade. Accordingly, we performed a series of investigations to evaluate it. EFNB2 expression was examined when NOTCH4 or NOTCH1 was downregulated, with or without DLL4 treatment. Then, the effects of NOTCH4 on EPC function were detected. Additionally, we analyzed NOTCH4 and EFNB2 expression in the EPCs from preeclampsia and normal pregnancies. Results showed that NOTCH4 downregulation led to decreased expression of EFNB2, which maintained the same level in the presence of DLL4/NOTCH activation. By contrast, NOTCH1 silencing resulted in a moderate increase in EFNB2 expression, which further increased in the presence of DLL4/NOTCH activation. The downregulation of NOTCH4 resulted in an increase of EPC biological activity, which was similar to EFNB2 silencing. NOTCH4 expression, consistent with the EFNB2 level, increased notably in preeclampsia EPCs compared with the controls. These findings suggest that NOTCH4, not NOTCH1, is the specific receptor for the DLL4/NOTCH–EFNB2 cascade. Blockade of this cascade may enhance the angiogenic property of EPCs, and act as a potential target to promote angiogenesis in patients with preeclampsia.